Analisis Target dan Realisasi Pajak Daerah di Kota Bogor dan Kabupaten Kuningan pada Tahun 2017–2024 - Osman, Dona Denise; Wiralaga , Harya Kuncara; Sebayang, Karuniana Dianta Arfiando (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the target and realization of local taxes in Bogor City and Kuningan Regency for the period 2017–2024, and to compare the revenue patterns before, during, and after the Covid-19 pandemic. This study employs a quantitative approach with comparative analysis, paired sample t-test, and one-way ANOVA. The results indicate that there is no significant difference between local tax targets and realizations across periods, suggesting that local tax revenue demonstrated sufficient resilience against economic shocks. However, descriptive analysis reveals differences in patterns between regions, where Bogor City as an urban area was more sensitive to changes in economic conditions, while Kuningan Regency with its agrarian characteristics showed more stable revenue. In terms of target achievement, Bogor City failed to meet its target twice, while Kuningan Regency failed six times throughout the study period. This study is expected to serve as a reference for local governments in formulating adaptive fiscal policies in accordance with the economic characteristics of their respective regions